Actividades manuales y habilidades visomotoras en los niños de la Institución Educativa Inicial N° 728 Mariscal Ramón Castilla 2024 - Luis Ruiz, Rosa Elizabeth (2025)
The main objective of this research is to explore the relationship between the degree of application of manual activities and the level of development of visual motor skills in the children of the Institución Educativa Inicial N°728, Mariscal Ramón Castilla, in the year 2024. This The study is carried out under a quantitative approach, of a relational and non-experimental nature, with a design To collect the data, the observation technique was used, supported by a specific guide designed for this purpose. This instrument was evaluated and validated by a committee of three experts in the field, who ensured its suitability to accurately measure the study variables. The results obtained using Spearman's correlation coefficient (Rho = 0.815) allow us to conclude that there is a positive and significant correlation between the variables analyzed, which reinforces the strength of the relationship found in the research.